Extracting epidemiological data from electronic medical record recording systems in United Kingdom primary care - Basra, Vishal (2017)
Electronic medical records (EMRs) in primary care represent a longitudinal record of patient’s current and past history and important health related data. The ability to use of electronic medical records from a variety of different sources is an important and growing area of research. This study aims to use participants in an existing cohort of patients (the Gedling study) and extract their GP health data into a usable research database.